Aru Shah and the End of Time [Aru Šah a koniec času anglicky]. Book 1. - Chokshi, Roshani, 1991- (Scholastic Children's Books, 2018)
Twelve-year-old Aru Shah has a tendency to stretch the truth in order to fit in at school. Whilst her classmates are jetting off to exotic locales, she'll be at home, in the Museum of Ancient Indian Art and Culture where her mother works. Is it any wonder that Aru makes up stories about being royalty, traveling to Paris, and having a chauffeur? When Aru's schoolmates dare her to prove that the museum's Lamp of Bharata is cursed, she doesn't think there's any harm in lighting it. Little does Aru know that lighting the lamp has dire consequences. She unwittingly frees the Sleeper, an ancient demon whose duty it is to awaken the God of Destruction. Her classmates and beloved mother are frozen in time, and, accompanied by a wise-cracking pigeon and her long-lost half-sister, it's up to Aru to save them..